Ḥayāh Dalam Kitab Al-Tafsīr Al-Bayāni Li Al-Qur'ān Al-Karīm - Irfansyah (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2024)
This study focuses on the study of the word hayah in the book Al-Tafsīr Al-Bayāni li Al-Qur'ān Al-Karīm by using Julia Kristeva's intertextuality as an analytical tool. This research reveals an academic biography that tracks the thoughts of Ā’isyah Bint Al-Syāti’. This study also reveals the explanation of the book and explores from an intertextual perspective the al-Kasyaf book as a source of reference from the book Al-Tafsīr Al-Bayāni li Al-Qur'ān Al-Karīm. in this study reveals some of the elements found, namely transposition, modification and demystification.